2021
DOI: 10.31219/osf.io/t2qey
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sedentarisation and maternal childcare networks: role of risk, gender and demography

Abstract: Worldwide mothers receive help with childcare from a diverse range of individuals (allomothers). Nonetheless, little exploration has occurred into why we see such diversity, such as different strategies used to buffer risk. Wide maternal childcare networks may be a consequence of situations of little material wealth and food storage - as is common in mobile hunter-gatherers - where households rely on the pooling of risk in informal insurance networks. In contrast, when households settle and accumulate wealth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…These results are consistent with the data that Starkweather et al [33] reported, in which mother and father account for 84.45% of all childcare, with their parents, older children and others accounting for a larger proportion of care than in fishing families. These results-in which women rely on childcare help from large, diverse networks of alloparents, who include non-kin-are also consistent with patterns of alloparenting across three groups in Sub-Saharan Africa [71] and with Agta women's alloparenting networks in the Philippines [72]. Finally, while our model result does not show a conclusive result about whether traders overlap work and childcare ties with kinship or not, it does generally suggest that traders are not favouring related trading partners as potential alloparents.…”
Section: (B) Cooperation Across Domains As An Adaptive Strategy For W...supporting
confidence: 66%
See 2 more Smart Citations
“…These results are consistent with the data that Starkweather et al [33] reported, in which mother and father account for 84.45% of all childcare, with their parents, older children and others accounting for a larger proportion of care than in fishing families. These results-in which women rely on childcare help from large, diverse networks of alloparents, who include non-kin-are also consistent with patterns of alloparenting across three groups in Sub-Saharan Africa [71] and with Agta women's alloparenting networks in the Philippines [72]. Finally, while our model result does not show a conclusive result about whether traders overlap work and childcare ties with kinship or not, it does generally suggest that traders are not favouring related trading partners as potential alloparents.…”
Section: (B) Cooperation Across Domains As An Adaptive Strategy For W...supporting
confidence: 66%
“…Despite the possibility that many Shodagor alloparents are engaged in less-intensive childcare tasks (e.g. [72]), their care is important. Shodagor women who have more alloparents available and also have a husband who provides childcare during the dry season are more likely to have reported currently working as traders [34], and children who receive care from both fathers and alloparents during the season when mothers trade experience better growth outcomes than children whose fathers provide care alone [33].…”
Section: (B) Cooperation Across Domains As An Adaptive Strategy For W...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, authors tested several novel predictions about how women's cooperation is influenced by socioecological context. For example, Page and colleagues ( [114], in this issue) hypothesized that women's childcare networks respond to major livelihood transitions. They predicted that in the shift from mobile to sedentary residence, childcare networks should decrease in size since wealth accumulates with sedentarism, reducing the need to rely on large networks of cooperators.…”
Section: (C) Variation In Women's Cooperation Reflects Need Risk and ...mentioning
confidence: 99%
“…In the Agta it appears that settlement does not have a simple, negative, relationship with cooperation. In terms of cooperation in childcare, a recent analysis highlighted that mothers' had the same or larger childcare networks (depending on the metric used to measure childcare) in settled camps compared to mobile camps, indicating little change in the amount of childcare support received (Page et al, 2021). Furthermore, more stable, settled camps were also associated with greater levels of reciprocal sharing in an experimental game, likely aided by the increase likelihood of future interactions between dyads (Smith et al, 2016).…”
Section: Discussionmentioning
confidence: 99%